The Effect of Kluwak Extract on Discoloration Nanohybrid Composite Resin - Ibrahim, Irsan; Alawiyah, Tuti; Dahayu Maheswari, Naura (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Background: Composite resin is the most commonly used restorative material in dentistry because it has good esthetics. However, consuming colored foods and drinks over a long period of time can cause discoloration. Kluwak, an ingredient often used in Indonesian cooking, contains tannins, which can change the color of the nanohybrid composite resin if consumed over a long period of time. Purpose: To determine and explain the effect of kluwak solution (pangium edule r) on the color change of nanohybrid composite resin. Methods and materials: The research was conducted experimental laboratory pre and post test. The number of samples was 30 nanohybrid composite resins with a diameter of 10 mm and a height or thickness of 2 mm, divided into 3 treatment groups, each group consisting of 10 samples with immersion for 1 day, 3 days, and 5 days in kluwak solution. Results: One way ANOVA test results (p<0.05) showed the effect of kluwak solution on hue color changes in nanohybrid composite resins. Conclusion: There is an effect of immersion in kluwak solution (pangium edule r) on nanohybrid composite resin.